MOLECULAR AND MORPHOLOGICAL ANALYSIS SUPPORTS THE TRANSFER OF THE MONOTYPIC INDONESIAN GENUS SEPTOGARCINIA KOSTERM. TO GARCINIA (CLUSIACEAE) - Rismita Sari; Darren Crayn; Natalie Dillon,; Paul Gadek; Sandra Abell (Reinwardtia, 2023)
Based on molecular phylogenetic analysis and an assessment of fruit and pollen characters, the transfer of Septogarcinia sumbawaensis Kosterm., endemic to Sumbawa Island, Indonesia and the sole member of the genus Septogarcinia, to Garcinia is strongly supported. The formal transfer of S. sumbawaensis to Garcinia (as G. sumbawaensis; the current name is G. septogarcinia) was based on morphological studies only. Phylogenetic analysis of nuclear internal transcribed spacer (ITS) sequences supports a placement of G. septogarcinia in Garcinia Section Brindonia. The distinctive dehiscent fruit, cited by Kostermans as justification for erecting Septogarcinia, is interpreted as an autapomorphy for this species in Garcinia. Pollen exine ornamentation is similar to G. griffithii, G. gummigutta var. gummi-gutta, G. mestonii, Garcinia sp. (Maluku) and Garcinia sp. (Batulanteh, Sumbawa).